Uma contribuição para a mensuração do Goodwill gerado internamente - Reis, Renato Maurício Porto (2013)
This Essay intends to discuss the concepts and issues related to Goodwill. For this it was presented the Goodwill role on the Financial Statements as an Intangible Asset. To achieve this goal it was made an analysis of the concepts indicated in the Brazilian Rules, specially the Technical Statement CPC 04 (R1) Intangible Assets and the Technical Statement CPC 15 (R1) Business Combination and the understanding that these rules plays in the registration and valuation of the Goodwill, especially in relation to the impossibility of its registration due to the many limitations of its concept. From the limits imposed by the accountant rules it was explored the main concepts proposed by the majors Authors and Professors about this theme and the conclusion that was presented by them that indicates a residual concept for Goodwill in merger and acquisitions. Once defined the limitations it can be stated that Goodwill can be defined as the overall force of the Identified Assets in a Company, therefore it will be explored a more complex and elaborate issue as the influence and proximity of the intellectual asset and the incorporate synergy. Made this considerations and known its effects, it was evaluated the concepts of the acquired Goodwill and the created Goodwill, in order to conclude that it is not the acquisition that creates the Goodwill it is latent and would be materialized and quantified when acquired. Therefore nothing would forbid that the created Goodwill would be calculated and registered. This would allow the best use by the stake holder of the Financial Statements. At the end it was proposed a quantification criteria and a way to incorporate this value in the Financial Statements